Identification of Nuisance Animals in Edible Bird's Nest Farming in Tanjung, North Lombok Regency - Septian, I Gede Nano; Aminurrahman, Aminurrahman; Karni, Ine; Amalyadi, Rezki; Gifari, Zaid Al (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The cultivation of edible bird's nest in North Lombok Regency is experiencing rapid growth. This can be attributed to the rising demand for edible bird's nest products. Nevertheless, the primary challenge to its advancement is the presence of nuisance animals. The objective of this study was to identify and categorise nuisance animals present in edible bird's nest cultivation sites within the boundaries of the Tanjung sub-district. The present study employed a descriptive qualitative approach, with data collection undertaken via purposive sampling. The findings of this study identified seven species of nuisance animals in edible bird’s nest cultivation in the area of Tanjung Subdistrict. The following animals are included in this category: snakes, rats, geckos, owls, bats, cockroaches, and ants. These animals have the capacity to exert a direct influence on the swiftlet population, thereby diminishing edible bird’s nest production, particularly within the confines of the Tanjung Subdistrict.